Latest trends in the assessment and management of paediatric snoring and sleep apnoea. Issue 5 (20th April 2016) - Sharma, S D; Kanona, H; Kumar, G; Kotecha, B
Abstract: Objective: To investigate the assessment and management of paediatric snoring and obstructive sleep apnoea in UK otolaryngology departments. Method: A telephone questionnaire survey of UK otolaryngology departments was conducted over a 16-week period. Results: The response rate was 61 per cent (85 out of 139 trusts). Use of pre-operative pulse oximetry was reported by 84 per cent of respondents, mainly to diagnose obstructive sleep apnoea (73 per cent) or stratify post-operative risk (46 per cent). Thirty-one per cent of respondents reported using post-operative pulse oximetry. Twenty-five per cent of respondents have a dedicated management protocol for paediatric obstructive sleep apnoea and snoring. Thirty-four per cent require prior clinical commissioning group approval before performing surgery. Fifty-eight per cent of respondents reported following up their obstructive sleep apnoea patients after surgery. The mean follow-up period (±standard deviation) was 6.8 ± 1.2 weeks. Conclusion: There is variation in the assessment and management of paediatric snoring and obstructive sleep apnoea across the UK, particularly in the use of pre- and post-operative pulse oximetry monitoring, and further guidelines regarding this are necessary.